Molecular detection of HEV in domestic pigs in Italy from Abruzzo and Molise regions. (20th October 2021) - Scattolini, S; Del Matto, I; D'Angelantonio, D; Rossi, F; Chiaverini, A; Piccioni, R; Antoci, S; Pomilio, F; Migliorati, G; Aprea, G
Abstract: Background: Hepatitis E virus (HEV) is a zoonotic pathogen transmitted through the faecal-oral route and it is responsible of disease in humans with more than 21.000 cases reported in the European Union (EU) over the last decade. It is a non-enveloped single stranded RNA virus that includes 8 genotypes; among these, genotypes 3 and 4 (HEV-3 and HEV-4) are the most prevalent in developed countries and infect both humans and some animal species such as domestic pigs. In this study, we investigated the prevalence of HEV in domestic pigs bred in Italy, in Abruzzo and Molise regions. Methods: During the period October 2020-March 2021, 327 liver samples from individual pigs were analysed. In particular, 211 were collected in 1 slaughterhouse and originated from animals bred in Abruzzo in 8 different farms and 116 were collected in 7 slaughterhouses and originated from animals bred in Molise in 47 farms. The real time retro-transcriptase (RT)-polymerase chain reaction (PCR) technique was used to detect HEV by targeting the open reading frame (ORF) 3 region of the viral ribonucleic acid (RNA). Results: None of the samples deriving from pigs bred in Abruzzo tested positive for the detection of HEV RNA. Instead, 4 samples from pigs bred in 2 different farms in Molise tested positive, showing a prevalence of 3.45%. Conclusions: Pigs are considered important reservoirs for HEV virus. For this reason, it is opportune to investigate the role of these animals for better understanding their involvement in the human infection through the consumption of contaminated raw or undercooked pork-meat products. These findings need to be further investigated with in depth genomic characterization of positive RNA samples to highlight the role of the specific strains circulating in this region and to draw conclusions about connections between animals, potential contaminated food and human disease. Key messages: The study paved the way for defining the role of pigs in the transmission of HEV virus to humans through the consumption of pork meat products. This study reports the prevalence of HEV in domestic pigs of Abruzzo and Molise regions, two Italian regions.